Interplay of oxidative stress and Inflammasome activation and clinical indices in Parkinson’s disease: insights from serum SIRT1, Nrf2, and NLRP3 levels and PDQ-39—a cross-sectional study - Aldossary, Khlood Mohammad; Hamza, Eman; Kamel, Mostafa M.; Alsegiani, Amsha S.; Alrubia, Sarah; Sarawi, Wedad S.; El-Khateeb, Eman; Eltantawy, Nashwa; Mourad, Shereen A.; Elshorbagi, Nora; Khrieba, Mohannad O. (Frontiers in Neuroscience, 2026)
BackgroundParkinson’s disease (PD) is a chronic, progressive neurodegenerative disorder characterized by heightened oxidative stress and persistent neuroinflammation. The sirtuin-1 (SIRT1) and nuclear factor erythroid 2–related factor 2 (Nrf2) pathways play key roles in maintaining antioxidant defense, whereas activation of the NLRP3 inflammasome drives inflammation-mediated neuronal damage. However, their systemic alterations and interrelations in PD remain incompletely characterized.ObjectiveTo determine and compare serum levels of SIRT1, Nrf2, and NLRP3 in patients with PD versus healthy controls and to analyze their correlations with fatigue severity and health-related quality of life indices.MethodsA case–control study was conducted on 60 participants, including 30 patients diagnosed with idiopathic PD and 30 age- and sex-matched healthy controls. Serum SIRT1, Nrf2, and NLRP3 levels were quantified using enzyme-linked immunosorbent assay (ELISA). Disease impact and fatigue were assessed using the Parkinson’s Disease Questionnaire-39 (PDQ-39) and Parkinson’s Fatigue Scale-16 (PFS-16), respectively. Statistical analyses included between-group comparisons, Spearman correlations, multiple linear regression, and receiver operating characteristic (ROC) curve analysis. Multiple comparison corrections were applied to ensure robustness of the findings.ResultsPD patients exhibited significantly lower SIRT1 (p = 0.0009) and Nrf2 (p = 0.0003) levels, and elevated NLRP3 (p = 0.006). HRQoL and fatigue were markedly impaired in PD patients across all domains (PDQ-39 SI median 47.06 vs. 11.88; PFS-16 total median 3.93 vs. 2.07; all p < 0.01). SIRT1 and Nrf2 levels were negatively correlated with PDQ-39 and PFS-16 scores, while NLRP3 showed positive correlations. Multiple linear regression revealed that SIRT1, Nrf2, NLRP3, and disease duration were independent predictors of HRQoL and fatigue severity. ROC analyses demonstrated excellent diagnostic performance for SIRT1 (AUC = 0.963) and high accuracy for Nrf2 (AUC = 0.913) and NLRP3 (AUC = 0.891).ConclusionPD is associated with impaired neuroprotection (SIRT1, Nrf2) and increased inflammation (NLRP3), which are closely linked to fatigue severity and diminished quality of life. These biomarkers independently predict clinical outcomes and show potential as minimally invasive diagnostic tools. Targeting oxidative stress and inflammasome-mediated inflammation may improve both molecular and clinical outcomes, highlighting the translational potential of the SIRT1/Nrf2/NLRP3 axis for personalized management of PD.